Tonal government in Igbo syntax. (July 2015) - Mbah, Boniface; Mbah, Evelyn
Abstract: Tone is widely reported as a prosodic feature of many African and Asian languages that contrasts meaning among words and sentential constructions. Hardly have any of the studies examined in detail the underlying syntactic principles which make it perform such functions. This article therefore investigates the principles which underlie the function of tone in the Igbo language, an East Benue Congo language, with particular emphasis on grammatical tone. This is done with the hope that the findings of the study can be inductively applied to other tone languages across the world. It answers such questions as: what are the principles which enable tone to perform its grammatical functions? What syntactic positions predispose tone to perform the grammatical functions? What are the grammatical realisations of tonal governance? The paper finds that tone is a constituent commander and governor. The principle of precede and constituent command (c-command) underlies tone governance. Just as in proper government, tone governs the lexical items, which it c-commands. The scope of tone and its domain of governance vary from one structure to another. The position of the governor determines its domain of governance and the kind of structure that is realised after governance. Such syntactic constructions as the negative, perfective, past tense, and serial verb constructions result from tonal government. Highlights: Tone is a constituent commander and governor. Tone governs the lexical items, which it c-commands. The scope of tone and its domain of governance vary from one structure to another. Constructions like the negative, perfective, past tense, and serial verb constructions result from tonal government.